1968
DOI: 10.2136/sssaj1968.03615995003200020023x
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Fixation by Amorphous Aluminosilica Gels

Abstract: Synthetic aluminosilica gels fixed potassium in varying amounts against replacement by common alkali and alkaline earth cations; the larger the solvated size of the replacing cation the greater was the amount of K retained. Replacing power thus followed the lyotropic series NH4 > Na > Ba > Ca > Mg. The amounts of K fixed against exchange by a particular ion increased with total cation‐exchange capacity (in turn dependent on gel composition) and with the pH value at which K‐saturation originally too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1969
1969
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…It cannot arise from permanent charge brought about by the presence of tetrahedral A1 in 2:1 allophane, because charge from isomorphic substitution does not affect the PZSE (Sposito, 1981); however, this may be due to other structural differences between imogolite and the 2.04 A1/Si allophane. The widely accepted structure of imogolite and allophane of 2:1 A1/Si is that of an outer gibbsite-like sheet pulled into a cylinder and sphere, respectively, by silica coordinated to the inside of the sheet (Cradwick et al, 197 2;van Reeuwijk and de Villiers, 1970). Nuclear magnetic resonance of z9Si in noncrystalline aluminosilicates has shown that both synthetic and natural materials consist ofimogolite-like structures in which the Si is directly bound to OH groups and allophane structures in which the Si is more fully polymerized and bound through oxygen to either A1 or Si ( Wilson et al, 1986;Goodman et al, 1985).…”
Section: Nature Of Titratable Sites In Imogolite and Allophanementioning
confidence: 99%
“…It cannot arise from permanent charge brought about by the presence of tetrahedral A1 in 2:1 allophane, because charge from isomorphic substitution does not affect the PZSE (Sposito, 1981); however, this may be due to other structural differences between imogolite and the 2.04 A1/Si allophane. The widely accepted structure of imogolite and allophane of 2:1 A1/Si is that of an outer gibbsite-like sheet pulled into a cylinder and sphere, respectively, by silica coordinated to the inside of the sheet (Cradwick et al, 197 2;van Reeuwijk and de Villiers, 1970). Nuclear magnetic resonance of z9Si in noncrystalline aluminosilicates has shown that both synthetic and natural materials consist ofimogolite-like structures in which the Si is directly bound to OH groups and allophane structures in which the Si is more fully polymerized and bound through oxygen to either A1 or Si ( Wilson et al, 1986;Goodman et al, 1985).…”
Section: Nature Of Titratable Sites In Imogolite and Allophanementioning
confidence: 99%
“…The structural models for amorphous aluminosilicares proposed by Cloos et al (1969) and van Reeuwijk and de Villiers (1970) provide a useful basis for understanding the surface charge characteristics of these materials. These models consider amorphous aluminosilicates to be composed of two intimately associated phases: an aluminosilicate phase resulting from the isomorphous substitution of tetrahedrally co-ordinated A1 for Si in a silica structure with a negative charge which is neutralized, at least partially, by a positively charged phase composed of hydroxyaluminium species.…”
Section: Synthetic Aluminosilicatesmentioning
confidence: 99%
“…(1964) confirmed the presence of tetrahedral A1 by X-ray fluorescence measurements. CEC variations with aluminosilicate composition have been explained by the models of Cloos et al (1969) and van Reeuwijk and de Villiers (1970), which consider amorphous aluminosilicates to consist of an aluminosilicate phase with permanent negative charge arising from isomo! 'phous substitution of A1 for Si, and a hydroxyaluminium phase with pH-dependent positive charge.…”
Section: Introductionmentioning
confidence: 99%
“…These gels were included for investigation because of the importance which has previously been attached (Cloos et al, 1969;van Reeuwijk and de Villiers, 1970) to their study as a means towards elucidating the nature and properties of allophane.…”
Section: Selective Dissolution By Other Reagentsmentioning
confidence: 99%